A Real-Business-Cycle model with human capital accumulation: Lessons for Bulgaria (1999-2018) - Aleksandar Vasilev (Macroeconomics and Finance in Emerging Market Economies, 2021)
We introduce human capital accumulation into a real-business-cycle setup. We calibrate the model to Bulgarian data for the period following the introduction of the currency board arrangement (1999-2018). We investigate the quantitative importance of the presence of skill acquisition for cyclical fluctuations in Bulgaria. After subjecting the model to a battery of tests, we find the quantitative effect of such a channel - aside from producing a moderate increase in the variability of hours - to be relatively small. In other words, government spending on education turns out to be an ineffective instrument when it comes to smoothing the cycle.
Keywords: E32; E24; H22; I21; 330; business cycles; human capital; Bulgaria